2000
DOI: 10.1007/s002510000205
|View full text |Cite
|
Sign up to set email alerts
|

Selection of T-cell epitopes from foot-and-mouth disease virus reflects the binding affinity to different cattle MHC class II molecules

Abstract: The major histocompatibility complex (MHC)-restricted selection of T-cell epitopes of foot-and-mouth disease virus (FMDV) by individual cattle MHC class II DR (BoLA-DR) molecules was studied in a direct MHC-peptide binding assay. By in vitro priming of T lymphocytes derived from animals homozygous for both MHC class I and II, five T-cell epitopes were analyzed in the context of three MHC class II haplotypes. We found that the presentation of these T-cell epitopes was mediated by DR molecules, since blocking th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
1

Year Published

2003
2003
2013
2013

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(24 citation statements)
references
References 0 publications
2
21
1
Order By: Relevance
“…FMD-VP2 and VP4, for example, were both demonstrated to bind with high affinity to BoLA-DRB3*1101 and BoLA-DRB3*0201, respectively. Moreover, their high binding affinity was consistent with their ability to stimulate lymphocyte proliferation [7]. In the present study, OVA peptides were demonstrated to have binding affinity for BoLA-DRB3*2703 ranging from 26.92 to > 320 µM.…”
Section: Discussionsupporting
confidence: 80%
See 4 more Smart Citations
“…FMD-VP2 and VP4, for example, were both demonstrated to bind with high affinity to BoLA-DRB3*1101 and BoLA-DRB3*0201, respectively. Moreover, their high binding affinity was consistent with their ability to stimulate lymphocyte proliferation [7]. In the present study, OVA peptides were demonstrated to have binding affinity for BoLA-DRB3*2703 ranging from 26.92 to > 320 µM.…”
Section: Discussionsupporting
confidence: 80%
“…Various OVA and FMD-V peptides have previously been used as immunogenic epitopes to define antigen presentation, the kinetics of peptide-MHC binding, and assess antibody responses of cattle and mice [3,4,7,11,17,22,31]. FMD-VP2 and VP4, for example, were both demonstrated to bind with high affinity to BoLA-DRB3*1101 and BoLA-DRB3*0201, respectively.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations